Optimizing assessment workload and student experience: a quantitative and qualitative analysis of an undergraduate subject restructure - Allsopp, Giselle Larissa; Wooding, Sarah Elizabeth; West, Jan Maree; Turner, Anne Isabella (Advances in physiology education, 2025)
We showed that reducing the number of assessment submissions did not initially decrease students’ perceived workload. Rather, producing more support materials for assessments and holding more support sessions by academic staff appeared to be most effective at fostering a positive student experience and students’ perception of academic workload. Optimizing the workload of university students is important for their academic performance and student experience. Large perceived workloads are associated with poorer academic performance and lower student satisfaction in university students.x In response to student feedback in 2021, we redesigned a second-year undergraduate physiology subject to optimize workload and improve student experience. The practical assessments (contributing 50% of the subject grade) were consolidated from five small reports to two more comprehensive reports. The new subject design resulted in a 3.85% reduction in practical assessment marks ( P < 0.05), although students maintained their academic performance on the end of the trimester quiz. Upon reflection, the new practical assessments may have been more challenging for students and more discriminating of academic performance, as they required greater levels of critical thinking and more in-depth discussion of complex physiological concepts. Student satisfaction was reduced following the first iteration of the new subject design, but with additional assessment support for students by academic staff in 2022, the student experience ratings were no longer below expected values. In summary, consolidating the number of practical assessments was predicted to foster deeper learning of physiological concepts. However, to successfully achieve this, support from academic staff appears to be an essential factor to foster a positive student experience. NEW & NOTEWORTHY We showed that reducing the number of assessment submissions did not initially decrease students’ perceived workload. Rather, producing more support materials for assessments and holding more support sessions by academic staff appeared to be most effective at fostering a positive student experience and students’ perception of academic workload.